Stimulasi Literasi Awal Anak Usia 5-6 Tahun: Efektivitas Aplikasi Membaca Berbasis Neurosains - Nurul Ismaya; Hosnol Hotimah; Agus Budiyono; Medi Yana (Institut Agama Islam Negeri Madura, 2026)
This study examines the effectiveness of a neuroscience-based reading application in stimulating early literacy among children aged 5-6 years at RA Asy-Syuhada' Pamekasan. The research employed a quasi-experimental design using a one-group pretest-posttest approach, involving 20 children selected through a total sampling technique. Data were collected using a performance-based assessment instrument developed based on the Early Childhood Development Achievement Standards (STPPA). The instrument was validated through expert judgment by two experts one in early childhood education and one in educational technology and was further supported by a practitioner in early childhood education. The results showed a significant improvement in early literacy scores, with the mean score increasing from 11.40 (moderate category) to 22.15 (high category), supported by a t-value of 14.98 and p < 0.001 at a significance level of 0.05. These findings indicate that the neuroscience-based reading application is effective in stimulating early literacy development through the activation of multisensory neural pathways involving visual, auditory, and motor processing in early childhood.